(untitled) (Tạp chí Y học Cộng đồng, 2026)
Objective: To describe the pattern of cardiovascular diseases in elderly inpatients at Thai Binh General Hospital from 2019 to 2023. Methods: A retrospective, cross-sectional study was conducted by reviewing all medical records of inpatients aged ≥60 years hospitalized with cardiovascular diseases between 01/01/2019 and 31/12/2023. Results: Over the 5 years, 47,731 hospitalizations of elderly patients due to cardiovascular conditions were recorded (50.9% male; 49.1% female). The overall mean age was 67.1 ± 15.2 years and increased gradually. The three most common disease groups were: other forms of heart disease (I30–I52) with 19,730 cases (in which arrhythmias accounted for 43.8% and heart failure 39.7%), hypertensive diseases (I10–I15) with 8,749 cases (70% essential hypertension), and ischemic heart diseases (I20–I25) with 7,102 cases (39.5% myocardial infarction and 36.6% angina pectoris). Among arrhythmias, atrial fibrillation and atrial flutter were the most common, accounting for 5,287 of 8,645 cases (61.2%). Conclusion: In elderly inpatients with cardiovascular diseases at Thai Binh General Hospital during 2019–2023, the most prevalent conditions were arrhythmias, heart failure, hypertension, and ischemic heart disease.